CONTRIBUTION OF PHYSICAL ACTIVITY, SLEEP QUALITY, AND COFFEE CONSUMPTION TO THE EVENT OF HYPERTENSION IN PEMALANG DISTRICT - suharyo suharyo; Fikhoh Nurlatifah (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
ABSTRACTOne non-communicable disease that is still a major health problem in developing countries is hypertension; the prevalence of hypertension reaches 25.8%. Unhealthy lifestyle changes are one of the important factors that cause hypertension in the community. The study was conducted to obtain information about the relationship between physical activity, sleep quality, and coffee consumption habits with hypertension at the age of 45-65 years in the Belik Public Health Center, Pemalang Regency. The Case-Control approach was released in the study. The research target is people aged 45-65 years who seek treatment at Belik Public Health Center. The number of samples taken purposively was 100 respondents divided into 50 for the case group and 50 for the control group. The Chi-Square test was used to analyze the relationship between variables and the OR value to determine the contribution of the independent variables. The results showed that 75% had moderate physical activity, 74% had poor sleep quality, and 70% had low coffee consumption. Variables related to the incidence of hypertension were physical activity (P-value = 0.032, OR = 11) and sleep quality (P-value 0.006, OR = 3.765), while the coffee consumption variable was not related. Increasing exercise habits and regulating quality sleep patterns should be a priority for health promotion efforts in hypertension management programs. Keywords : Physical Activity, Hypertension, Coffee Consumption, Sleep Quality